2018
DOI: 10.1089/hum.2017.080
|View full text |Cite
|
Sign up to set email alerts
|

Development of Anti-Human Mesothelin-Targeted Chimeric Antigen Receptor Messenger RNA–Transfected Peripheral Blood Lymphocytes for Ovarian Cancer Therapy

Abstract: CD19-targeted chimeric antigen receptor (CAR) engineered T/natural killer (NK)-cell therapies can result in durable clinical responses in B-cell malignancies. However, CAR-based immunotherapies have been much less successful in solid cancers, in part due to "on-target off-tumor" toxicity related to expression of target tumor antigens on normal tissue. Based on preliminary observations of safety and clinical activity in proof-of-concept clinical trials, tumor antigen-specific messenger RNA (mRNA) CAR transfecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 50 publications
0
56
0
1
Order By: Relevance
“…[46][47][48][49][50] Many clinical trials and experimental therapies have targeted these two tumor markers, including vaccine, CA125/MUC16-or mesothelin-specific antibody and CAR T cell therapy. [51][52][53][54][55][56] Therefore, with these markers highly expressed in our model, this novel system physically recapitulates human HGSC development and spread, allowing for the preclinical screening of new therapies targeting CA125, mesothelin and many other markers.…”
Section: Discussionmentioning
confidence: 98%
“…[46][47][48][49][50] Many clinical trials and experimental therapies have targeted these two tumor markers, including vaccine, CA125/MUC16-or mesothelin-specific antibody and CAR T cell therapy. [51][52][53][54][55][56] Therefore, with these markers highly expressed in our model, this novel system physically recapitulates human HGSC development and spread, allowing for the preclinical screening of new therapies targeting CA125, mesothelin and many other markers.…”
Section: Discussionmentioning
confidence: 98%
“…Using a model system of HIV, they generated nef-and gag-specific TCRs, and their work uncovered interesting functionality about expressing TCRs with different specificities on the same T lymphocyte. One TCR seemed to be dominant, in this case, the nef-specific TCR; in order Hodgkin's lymphoma 52 Mesothelin mesothelioma 33,34,49 mesothelioma, pancreatic cancer 35 pancreatic cancer 36 ovarian cancer 37 MCSP melanoma 40,41 Her-2/neu ovarian cancer 13,14 ErbB2 Review to have both TCRs functioning independently, the dominant TCR had to be altered with murine co-stimulatory domains. In 2018, Campillo-Davo et al 23 investigated the function of mRNA-encoded TCR after removing the endogenous TCR by RNAi.…”
Section: Ivt Mrna For Expanded T Cells and Engineered Tcrsmentioning
confidence: 93%
“…Again, evaluation of patients' sera showed a spreading antibody response with increased antibody production against multiple proteins including several immunoregulatory molecules such as programmed cell death protein 1 (PD1), programmed death ligand 1 (PDL1), and B cell maturation antigen (BMCA). Finally, Hung et al 37 at Johns Hopkins University recently reported a new technique for production of mesothelindirected mRNA CAR T cells that uses unselected and unexpanded PBMCs that are cryopreserved after large-scale manufacturing. Using a murine model of ovarian cancer, equally good efficacy could be demonstrated when either cryopreserved or freshly made mRNA CAR T cells were injected.…”
Section: Ivt Mrna Car T Cells Targeting Solid Malignancies Car-encodimentioning
confidence: 99%
“…A previous study has shown that median receptor expression 24 h after electroporation with the corresponding mRNA was 82.0% and NK cells transfected under such conditions had significant cytotoxicity in xenograft cancer model [51]. Recently, a study indicated that "on-target off-tumor" toxicity, which is a critical factor limiting the application of CAR-based immunotherapies, may be effectively avoided by transduction with mRNA [52]. Nevertheless, the anti-tumor effect of CAR-NK cells transferred by mRNA electroporation may be transient because the expression of CARs transferred in this way is no more than 3 days [53].…”
Section: Car Transduction Into Nk Cellsmentioning
confidence: 99%